Disfungsi Smartphone dalam Proses Belajar Mengajar di SMAN 02 Ranah Batahan Kabupaten Pasaman Barat - Roza, Afrina; Wahyuni, Yanti Sri; Yatim, Yenita (Lembaga Yasin AlSys, 2023)
This research was motivated by the problem of Smartphone Dysfunction in the Teaching and Learning Process and looked at the teaching and learning process in the classroom, at SMAN 2 Ranah Batahan, West Pasaman Regency. This research aims: 1) to describe Smartphone Dysfunction in the Teaching and Learning Process. This research uses functional structural theory from Robert K Merton. Structural functionalism is a broad viewpoint in sociology and anthropology that attempts to interpret society as a structure with interconnected parts. The type of research used is descriptive with a qualitative approach. The informants in this research were, Class West Pasaman. Data collection techniques in this research are observation, interviews and documentation. Data analysis techniques include data reduction, data presentation, and drawing conclusions. The results of this research show that, Smartphone Dysfunction in the Teaching and Learning Process at SMAN 2 Ranah Batahan, West Pasaman Regency has several Smartphone Dysfunctions, namely: 1) Smartphones are used for entertainment, 2) Smartphones are used to develop network friendships by students.